Dual Role of Argyreia speciosa in Gastric Ulcer Management: A Study on Gastric Ulcer Protective and Healing action in Albino Mice. - Srivastava, Awanish kumar; Sharma, Rajesh kumar; Singh , Brijesh (Journal of Neonatal Surgery, 2025)
The rasayana herb Argyreia speciosa (Convolvulaceae), also referred to as Vruddhadaruka, is utilized in numerous ayurvedic treatments within the Indian medical system. The roots of A. speciosa are employed in Ayurveda as a tonic for general ability, aphrodisiac, nervine tonic, brain tonic, intellect boosting, and in hepatomegaly. According to reports, the plant contains anti-inflammatory, antibacterial, immunomodulatory, wound-healing, and nootropic effects. Argyreia speciosa (Convolvulaceae) was tested for its ability to prevent and treat ethanol-induced stomach ulcers in rats. For five days before or after ulceration, ethanolic versions of the apical plant tissues (200 mg/kg of body weight) was administered orally every day. An oral dose of 1 mL pure ethanol was given on 24-hour empty stomachs. Three groups of mice were created. The control group was Group 1. Each extract was given into groups 2 and 3. Measurements of ulcer indices, such as acidity of the stomach and volume and lesion counts, were used for the evaluation. To ascertain the stomach's histological evaluation, the work was prolonged. The ulcer index was significantly elevated in cases of gastric ulcer. The medicinal efficacy of the ethanol extract was higher. To sum up, A. speciosa had antiulcer properties. To determine which chemicals are causing the pharmacological impact, further thorough research is needed..